A design method of selecting gear ratios in manual transmissions of modern passenger cars. (February 2019) - Bera, Piotr
Highlights: Gear ratios are calculated based on the basic vehicle parameters. The whole method consists of a few consecutive steps, which are described in detail. The formulas allow a vehicle to be designed with regard to dynamics and fuel economy. The method enables simple and precise calculation of intermediate gear ratios. Two stage calculations allow this method to be used by amateurs and professionals. Abstract: The objective of this paper is to present an algorithm of gear ratio calculation in the manual transmissions of modern passenger cars. The paper presents all the necessary coefficients and formulas and thoroughly explains their influence on particular features of the vehicle, which are closely connected with its expected exploitation. These formulas result both from physical relationships and the performed analysis of vehicle dynamics, fuel economy, ergonomics and road characteristics. Every type of combustion engine, SI naturally aspirated, SI turbocharged or CI turbocharged, can be considered as vehicle propulsion. Particular emphasis is placed on a new method of gear spacing, which enables the simple and precise adjustment of intermediate gears. To quantitatively assess the dynamics and fuel economy of a specific construction, formulas for drawing the full throttle power characteristic and the characteristic of specific fuel consumption are provided. Moreover, a short and effective formula for calculating maximum vehicle speed has been developed. At the end of the work, there is a calculation example, which is an integral part of the article, showing the presented method on a particular vehicle.